Facile access to chelating CAArC-phosphine (CAArCPhos) palladium complexes - Leistikow, K. Georg; Wingelstern, Alexander; Rohrmann, Philipp; Wunsch, Jonas; Werst, Jan; Brückner, Margit; Rominger, Frank; Rudolph, Matthias; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2025)
In this article, we present a synthetic route to 4-(diphenyl-phosphino) isoindolium salts based on a new protecting group strategy. Key to success is the use of hemi-aminal methyl ether precursors, which serve as base-stable iminium salt equivalents that enable halogen-metal exchange and subsequent functionalization. After removal of the protecting group, the catalytically active palladium(II) complexes are formed of phosphine isoindolium salts by a CMD-like metalation process, producing the first examples of chelating cyclic amino(aryl) carbene complexes. Calculations on the mechanism support an acetate-assisted intramolecular palladation of the cyclic amino(aryl) carbene-phosphine (CAArCPhos) ligand enabled by the phosphine directing group through a six-membered transition state.
Erstveröffentlichung: 15. Oktober 2025
Gesehen am 22.01.2025